Metformin degradation with catalytic ozonation and/or catalytic CeO2 process - Liew, Kelvis Yu Ze (Nanyang Technological University, 2023)
Diabetes is one of the world’s most common diagnose disease and it is increasing at an alarming rate. Studies have projected that by 2045, 783 million people in the world will be diagnose with diabetes. Among the type of diabetes, Type II diabetes is the most common which predominate over 90% of the total global diabetic cases. Metformin drug has been widely used to treat and control Type II diabetes. However, studies have shown that the metformin drug cannot be fully metabolized in the human body and metformin is excreted out from the human body during urination. Metformin is then transferred into the municipal treatment plant which its conventional treatment process is unable to completely remove the Metformin. Thus, leaving trace elements of Metformin in surface water. In recent years, studies have found that metformin is an emergent endocrine disruptor compound which can significantly cause harm to living organism ‘s reproductive system. Moreover, there have been reports of trace elements of metformin found in surface water which may lead to bioaccumulation. This bioaccumulation of metformin can threaten the human health and aquatic environment. Therefore, there is a urgent need to develop an effective method of treating Metformin in wastewater treatment plant. Most studies have involved the use of advanced oxidation process such as UV irradiation and ozonation. This final year project will be a continuation of the previous FYP research regarding the effectiveness of catalytic ozonation using CeO2 catalyst to remove Metformin as it is still incomplete. The objective of this project will investigate the parameters and catalyst loading that will affect the degradation and mineralization of metformin through catalytic ozonation. The parameters involve are initial concentration of Metformin, catalyst loading with and without (UVC @ 256nm) pretreatment, ozone feed rate and pH level. The result of Metformin degradation effectiveness is carried out through UV-Vis Spectroscopy while the mineralization effectiveness of metformin effective is carried out through TOC analyzer. The experimental result show that Metformin was not completely degraded for all initial Metformin (1mg/L to 5mg/L). It is found that increasing the initial concentration of metformin will only reduce the degradation effectiveness of Metformin. Similarly, significant reduction of degradation percentage was found to have half from 3mg/L to 4mg/L of initial concentration of Metformin. Increasing concentration of CeO2 catalyst without UV pretreatment or increasing.